Divergent phenotypes in Gaucher disease implicate the role of modifiers - Goker-Alpan, O (BMJ Group, 2005)
Background: Gaucher disease is classified into neuronopathic and non-neuronopathic forms with wide phenotypic variation among patients sharing the same genotype. While homozygosity for the common L444P allele usually correlates with the neuronopathic forms, how a defined genotype leads to a phenotype remains unknown. Results: Residual enzyme activity was highly variable and did not correlate with the observed clinical course. There was also a wide spectrum of phenotypes. Average age at diagnosis was 15 months, and slowed saccadic eye movements were the most prevalent finding. The most severe systemic complications and highest mortality occurred in splenectomised patients before the advent of enzyme replacement therapy (ERT). On ERT, as morbidity and mortality decreased, developmental and language deficits emerged as a major issue. Some trends related to ethnic background were observed. Conclusion: The wide clinical spectrum observed in the L444P homozygotes implicates the contribution of genetic modifiers in defining the phenotype in Gaucher disease.